Factors associated with pre-lacteal feeding practices among mothers having children aged 0-36 months in bangladesh: evidence from Bangladesh Demographic and Health Survey 2017-18 - Sultana, F; Sheba, IT (SAGE Publications, 2022)
Despite being a known barrier to optimal breast-feeding indicators, the practice of Pre-lacteal Feeding (PLF) remains a key challenge in Bangladesh. This study examines the prevalence and underlying factors associated with PLF, for which data from a weighted sample of 4982 Bangladeshi mothers with children aged 0 to 36 months from the 2017-18 Bangladesh Demographic and Health Survey was used. Step-by-step multivariate logistic regression was performed to identify the association of significant determinants of PLF practices. Nearly 29% newborns received PLF before breastmilk and timely initiation of breastfeeding did not happen in case of 20.5% babies. The odds of PLF were significantly higher among the inhabitants of Dhaka division compared to other regions. In addition, birth-related factors such as optimal ANC visits (P < .01), home delivery (P < .01) and delivered by cesarean section (P < .01) showed significantly higher odds of introducing PLF to the newborns. Our results demonstrated the need for developing targeted policies and actions to prevent such practices of PLF in order to improve optimal breastfeeding behavior in Bangladesh.